Pressurized PEM water electrolysis: Dynamic modelling focusing on the cathode side. (22nd January 2022) - Correa, G.; Marocco, P.; Muñoz, P.; Falagüerra, T.; Ferrero, D.; Santarelli, M.
Abstract: This paper describes a lumped dynamic model for a high pressure PEM water electrolyzer. Since the electrolyzer under analysis is characterized by unbalanced pressure configuration with high cathodic working pressure, the model focuses on the cathode side to adequately predict the electrolyzer performance, analyzing and highlighting the importance of the cathodic activation overpotential term. The model is calibrated using experimental data from a 5.6 kW PEM water electrolyzer stack. A very good fit can be observed between the model and the experimental data, not only at different temperatures, but also at different pressures. It is found that the rise of temperature affects mainly the ohmic overpotential, while increasing the cathode pressure leads to an increment in the cathode activation overpotential that is not negligible for the electrolyzer performance. By rising the operating current, the cathode activation overpotential becomes 63% of that of the anode (at 70 bar, 1.2 A/cm 2 and 50 °C). Highlights: Dynamic model of PEM electrolyzer stack with unbalance pressure configuration. Model calibrated with experimental data from a 5.6 kW PEM water electrolyzer stack. Modeling of pressure influence on the activation overpotential term. Non negligible contribution of cathodic activation overpotential at high pressure. Voltage increase when increasing pressure mainly due to activation overpotential.